Two Faces of Transcendental Empiricism: Gilles Deleuze and John McDowell - Danila A. Volkov; Maksim D. Evstigneev (RUDN Journal of Philosophy)
The research presents a comparative analysis of John McDowell’s and Gilles Deleuze’s conceptions of transcendental empiricism. The very name of this conception bears in itself a kind of paradox, since Kant (the father of transcendental philosophy) occasionally used the term “transcendental” as “non-empirical”. The research presents an attempt to explain why these philosophers apply to themselves such self-description and how they understand it. To achieve this goal, we present an analysis of transcendental empiricism of each of the heroes of the study. An analysis of Deleuze’s view shows that he considers transcendental empiricism as a study of the validity of our experience. The main question of Deleuze’s transcendental philosophy is Kant’s quid juris? We also show that Deleuze’s transcendental empiricism is a self-conscious attempt to develop post-Kantian and phenomenological traditions in modern philosophy that stands in sharp opposition to any form of Hegelianism. McDowell, contrary to that, is more sympathetic to Hegel. His transcendental empiricism has another roots from that of Deleuze. It is motivated by Sellar’s critique of “the Myth of the Given” and McDowell’s attack on the “third dogma of empiricism”. These projects show the inconsistency of traditional empiricism. However, according to McDowell, they do not show the impossibility of non-traditional, transcendental empiricism that is concerned with the question of the very possibility of empirical worldview. The comparative analysis of McDowell’s and Deleuze’s projects show, despite the difference of philosophical tradition and style, close affinity between some moves of these philosophers. However, it also reveals some important differences. While McDowell is seeking to show how the concepts can be actualized in intuitions, the main concern of Deleuze is to show how intuition can develop itself into conceptual form